Applications of Lipid based Formulation Technologies in the Delivery of Biotechnology-based Therapeutics - H. du Plessis, Lissinda; B. Marais, Etienne; Mohammed, Faruq; F. Kotze, Awie (Current Pharmaceutical Biotechnology, 2014)
In the last decades several new biotechnologically-based therapeutics have been developed due to progress in genetic engineering. A growing challenge facing pharmaceutical scientists is formulating these compounds into oral dosage forms with adequate bioavailability. An increasingly popular approach to formulate biotechnology-based therapeutics is the use of lipid based formulation technologies. This review highlights the importance of lipid based drug delivery systems in the formulation of oral biotechnology based therapeutics including peptides, proteins, DNA, siRNA and vaccines. The different production procedures used to achieve high encapsulation efficiencies of the bioactives are discussed, as well as the factors influencing the choice of excipient. Lipid based colloidal drug delivery systems including liposomes and solid lipid nanoparticles are reviewed with a focus on recent advances and updates. We further describe microemulsions and self-emulsifying drug delivery systems and recent findings on bioactive delivery. We conclude the review with a few examples on novel lipid based formulation technologies.
Keywords: solid lipid nanoparticles